In vitro and in vivo Evaluation of Succinic Acid-Substituted Mesoporous Silica for Ammonia Adsorption: Potential Application in the Management of Hepatic Encephalopathy - Mohammadi H (Dove Medical Press, 2020)
Hamidreza Mohammadi,1,2 Reza Heidari,1 Seyyed Vahid Niknezhad,1 Akram Jamshidzadeh,1,2 Fatemeh Farjadian1 1Pharmaceutical Sciences Research Center, Shiraz University of Medical Sciences, Shiraz, Iran; 2Department of Pharmacology and Toxicology, Faculty of Pharmacy, Shiraz University of Medical Sciences, Shiraz, IranCorrespondence: Fatemeh FarjadianPharmaceutical Sciences Research Center, Shiraz University of Medical Sciences, P. O. Box 158371345, Karafarin Ave., Shiraz, Fars, IranTel + 987132424127 302Fax + 987132424126Email farjadian_f@sums.ac.irAkram JamshidzadehDepartment of Pharmacology and Toxicology, Faculty of Pharmacy, Shiraz University of Medical Sciences, P. O. Box 158371345, Karafarin Ave., Shiraz, Fars, IranEmail ajamshid@sums.ac.irPurpose: Hepatic encephalopathy (HE) is a critical situation in which liver failure affects brain function. HE could result in a state of coma and death. The liver is the main organ for ammonium ion (NH4+) metabolism. Hence, acute and/or chronic liver failure could lead to hyperammonemia. NH4+ is the most suspected neurotoxic agent in HE. Thus, finding new therapeutic options to decrease plasma and brain NH4+ levels has a significant clinical value. Mesoporous silica (MS) particles have revolutionized many aspects of pharmaceutical sciences, including drug delivery systems. Moreover, recently, MS has been applied as agents for the detoxification of chemicals (eg, drugs and poisons).Methods: First, MS particles containing amine groups (MS-NH2) were synthesized in co-condensation processes. Then, the structure was modified by succinic anhydride to have MS-SA. The MS-SA was characterized (FT-IR, XRD, X-ray photoelectron spectroscopy (XPS), DLS-Zeta FESEM-EDX, and HRTEM). Then, the potential of MS-NH2 and MS-SA particles in adsorption of NH4+ was investigated in vitro and in vivo. MS-NH2 and MS-SA were incubated with increasing concentrations (0.1– 10 mM) of NH4+, and the scavenging capacity of the investigated particles was evaluated. On the other hand, different doses (1 and 5 mg/kg per day) of nanoparticles were administered to a hyperammonemia animal model.Results: It was figured out that both MS-NH2 and MS-SA significantly scavenged NH4+ in the in vitro model. However, the NH4+ scavenging capability of MS-SA was more significant. Administration of MS-NH2 and MS-SA also considerably decreased the level of ammonium in plasma and brain and improved cognitive and locomotor activity in hyperammonemic animals. The effects of MS-SA were more significant than MS-NH2 in the HE animal model.Conclusion: Collectively, our data suggest that MS particles, especially succinic acid-functionalized MS, could act as special ancillary treatment in HE as a critical clinical complication.Keywords: acute liver failure, ammonia, hyperammonemia, nanomedicine